Intelligent Transport Systems From Research and Development to the Market Uptake Third EAI International Conference, INTSYS 2019 - Martins, A.; Ferreira, J. (2020)
We are delighted to introduce the proceedings of the second edition of the International Conference on Intelligent Transport Systems (INTSYS 2019) from the European Alliance for Innovation (EAI). This conference brought together researchers, developers, and practitioners from around the world who are leveraging and developing Intelligent Transportation Systems (ITS) to increase efﬁciency, safety, mobility, and tackle Europe’s growing emission and congestion problems. The theme of INTSYS 2019 was “Intelligent Transport Systems (ITS) has the Edge on Innovation.” The technical program of INTSYS 2019 consisted of 20 full papers, presented in oral sessions at the main conference tracks, and selected out of 35 submission received. All of the accepted papers were subjected to a blind peer-review process with a minimum of four reviews for each paper. Concerning the committees, it was a great pleasure to work with the excellent organizing team of the EAI, which was absolutely essential for the success of the INTSYS 2019 conference. In particular, we would like to express our gratitude to Kristina Lappyova and Marek Kaleta for all the support they provided in all subjects. We would like also to express our gratitude to all the members of the Technical Program Committee, who have helped in the peer-review process of the technical papers, as well as ensured a high-quality technical program. We would like to thank the extensive list of external reviewers from several areas of expertise and from numerous countries around the world. A special acknowledgement has to be addressed to all the authors for their effort producing such good quality papers and also for the extremely rich and positive feedback shared at the conference. We strongly believe that the INTSYS conference provides a good forum for all researcher, developers, and practitioners to discuss all science and technology aspects that are relevant to ITS. We also expect that the future INTSYS conferences will be as successful and stimulating, as indicated by the contributions presented in this volume. January 202